APLIKASI PEMBELAJARAN PAI (PENDIDIKAN AGAMA ISLAM) METODE IBL (INQUIRY BASED LEARNING) BERBASIS ZONE ACTIVITY DI SEKOLAH DASAR LEBAH PUTIH SALATIGA - Wahyu Budi Utomo (Universitas Muhammadiyah Surakarta, 2020)
The purpose of this study is to describe the application of Islamic religious education learning with zone based activity inquiry based learning methods implemented at SD Lebah Putih Salatiga. This research is a field research. The method used by researchers in compiling this research is a descriptive qualitative method, with a taxonomic analysis (classification) model based on focus on one domain, and only one characteristic in common. Data collected through observation, interviews, and documentation. The results of this study are applications of Islamic religious education learning with zone based activity inquiry based learning methods applied at SD Lebah Putih Salatiga, namely by making learning classified according to the abilities of each student, such as: the ability to read and write the Koran, the ability memorize short letters and the ability to understand the context of the teachings of the Koran in daily life (according to age level). Classification of abilities in understanding religion is prioritized not just in class level classification, as most schools present Islamic religious education normally. At SD Lebah Putih the learning is called Zone Activity which is a development of Morning Activity. The implementation of zone activity-based PAI learning is carried out with the following steps, such as: designing lesson plans, implementing and evaluating.